Jumandy, le héros national des Napo Runa : généalogie de la création d’un héros amazonien - Arthur Cognet (Bulletin de l'Institut Français d'Études Andines, 2021)
In this paper we describe the creation process of an Amazonian hero. Jumandy was one of the leaders of an indigenous rebellion against the Spaniards that took place in 1578 in the upper Napo area. Jumandy was discovered in archives by historians and ethnologists, and then established as a hero by the non-indigenous social elite of the Napo Province. Subsequently, the Napo Runa of the Ecuadorian Amazon adopted him as their hero in the context of the indigenous nationalist movement’s development. However, the vision of the hero Jumandy developed by the Napo Runa is different from the vision promoted by the non-indigenous social elite.